"Follow the wise" : studies in Jewish history and culture in honor of Lee I. Levine - Levine, Lee I.; Weiss, Zeev, 1959- (Eisenbrauns, 2010)
In 1961, when Lee Israel Levine graduated from both Columbia College in New York, majoring in philosophy, and Jewish Theological Seminary, majoring in Talmud, this accomplishment was only a precursor to the brilliant career that would follow. While researching his Columbia University dissertation in Jerusalem, Levine established close ties with members of the Institute of Archaeology at Hebrew University and Prof. Yigael Yadin, who recognized the need for an interdisciplinary approach that would give graduate archaeology students a solid base in Jewish history and rabbinic sources to supplement their archaeological training. Levine accepted Yadin's invitation to return to Israel after graduation to teach at the Institute of Archaeology and later was granted a joint appointment in the Institute of Archaeology and the Department of Jewish History. In 1985, he was promoted to the rank of Full Professor, and since 2003, he has held the Rev. Moses Bernard Lauterman Family Chair in Classical Archaeology at the Hebrew University. Levine was instrumental in founding and developing the TALI (an acronym for Tigbur Limudei Yahadut, Enriched Jewish Studies) track of Israel's state school system. He was also a founding member of the Seminary of Judaic Studies in Jerusalem (now known as the Schechter Institute for Jewish Studies), which opened its doors in 1984. In addition to teaching, Lee headed the Schechter Institute (first as dean and then as president) from 1987 to 1994. Lee was an active member of the Masorti Movement in Israel and represented it abroad as Director of the Foundation for Masorti Judaism (1986-87) and Vice-Chancellor of Israel Affairs at the Jewish Theological Seminary (1987-94). The honoree has published 12 monographs, 11 edited or coedited volumes, and 180 articles. His scholarship encompasses a broad range of topics relating to ancient Judaism, especially archaeology, rabbinic studies, and Jewish history. Within these disciplines he has dealt with a variety of subfields, including ancient synagogues and liturgy, ancient Jewish art, Galilee, Jerusalem, Hellenism and Judaism, and the historical geography of ancient Palestine. He is one of the first major scholars to draw on and integrate data from all of these fields in order to afford a better understanding of ancient Judaism. The 32 contributions to this volume by 35 authors are a tribute to his influence on this field of study and reflect the broad spectrum of his own interests. The 26 English and 6 Hebrew essays are divided into sections on Hellenism, Christianity, and Judaism; art and archaeology--Jerusalem and Galilee; rabbis; the ancient synagogue; sages and patriarchs; and archaeology, art, and historical geography.